Analysis of Transportation Method in Optimization of Distribution Cost Using Stepping Stone Method and Modified Distribution - Annisa; Mardiningsih (Journal of Mathematics Technology and Education, 2021)
This study aims to examine each method to show the characteristics, advantages and disadvantages of the transportation problem solving method. Vogel Approximation Method (VAM) is an initial solution method that is better than other methods and generally produces an initial solution that is close to the optimum result. In this study the Stepping Stone and Modified Distribution methods produce the same total cost. The main difference between these two methods is in the step of using the shortest path. The author concludes that the determination of the optimal method must be adapted to the conditions of the transportation problem to be solved. The meaning depends on the number of problem variables which will include the number of sources, the number of destinations and the time provided to solve the transportation problem.